Pengaruh Metode Penyuluhan KB Berbasis Multimedia Terhadap Pengetahuan Dan Minat Wanita Usia Subur Dalam Menggunakan IUD Di Puskesmas Muara Enim Palembang - Ana Yuliana; Novita Novita (Jurnal Ners, 2025)
The knowledge and interest of women of reproductive age in contraceptive methods for family planning (FP) are significantly influenced by the counseling methods used. This study aims to analyze the effect of multimedia-based FP counseling on the knowledge and interest of women of reproductive age in using intrauterine devices (IUDs) at Muara Enim Health Center, Palembang. This research employs a pre-experimental design with a One-Group Pretest-Posttest approach. The study sample consists of 50 women of reproductive age who received multimedia-based FP counseling. Data were collected using a questionnaire to measure knowledge and interest before and after the counseling session. The results show a significant increase in participants' knowledge and interest regarding IUD use after receiving multimedia-based counseling. Data analysis using the T-test indicates that multimedia-based counseling has a positive effect on the knowledge and interest of women of reproductive age in choosing IUD contraception. Therefore, this counseling method can be an effective alternative to enhance the knowledge and interest of women of reproductive age in using contraceptive methods, particularly IUDs, at Muara Enim Health Center, Palembang.